Environmental Sustainability in Next-Generation Hospitals. Identifying Needs and Requirements from Healthcare Organizations and Industry Stakeholders. - Dolcini, Michele; Brambilla, Andrea; Mangili, Silvia; Capolongo, Stefano (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Hospitals are among the most resource-intensive infrastructures, consuming significant amounts of energy, water, and materials while contributing 5.2% of global carbon dioxide emissions. Despite growing awareness and international commitments, hospitals face financial, structural, and operational barriers in implementing sustainability strategies. Study design. The study assesses the maturity of healthcare stakeholders regarding environmental sustainability, exploring key drivers, barriers, and strategies for integrating sustainability into healthcare facilities. Methods. A national web-based survey was conducted within the Joint Research Partnership Healthcare Infrastructures between November 2022 and January 2023, gathering 30 responses from 32 partners (94% participation rate). The analysis focuses on the environmental sustainability dimension, using descriptive statistics to identify trends, challenges, and best practices. Results. Healthcare stakeholders selected the most relevant Sustainable Development Goals for hospitals. Sustainability is widely recognized as a priority, yet resource allocation emerges as marginal. The most frequently cited constraint for improving environmental sustainability was financial constraints (n=27/30). Indeed, some hospitals are implementing energy-efficient retrofitting, high-efficiency thermal power plants, and sustainability building certification. The adoption of Building Energy Management Systems and retrofit interventions to maximise energy efficiency suggests increasing interest in sustainability performance measurement. Conclusions. Despite growing awareness, financial and regulatory support must be strengthened to facilitate hospital sustainability investments. Early integration of sustainability principles, access to public and private models and multi-stakeholder collaboration are crucial. Future research and action should foster multi-stakeholders approaches, develop sector-specific sustainability frameworks and assess the long-term impact of sustainability initiatives in healthcare.